Economic diplomacy and conflict resolution: Harnessing the economic peace leverage theory in the Palestine-Israel context - Fahlevi, Mochammad (Journal of Economics and Business Letters, 2023)
The Palestine-Israel conflict, commencing on October 7th, has led to significant human and economic repercussions, with Palestine facing dire economic challenges exacerbated by multiple factors, and Israel experiencing disruptions in sectors such as construction. The paper delves into the Economic Peace Leverage Theory (EPLT), positing that economic tools can foster peace and reduce conflicts. The global Boycott, Divestment, and Sanctions (BDS) movement, aiming to influence Israel's policies towards Palestinians, aligns with EPLT's principles, drawing from historical instances like the South African anti-apartheid struggle. Despite Israel's resilient economy, BDS holds symbolic significance, influencing global narratives. The paper emphasizes that the real impact of BDS lies more in its perceptual influence than economic setbacks for Israel. To harness EPLT's potential and address the root concerns of the BDS movement, a collective global effort is vital. Such collaboration can pave the way for sustained peace and prosperity in the region.